DEVELOPMENT OF BASIC MOVEMENT MODEL BASED ON INTERACTIVE MULTIMEDIA FOR ELEMENTARY STUDENTS - Arief Darmawan; Muh. Asmawi (Program Pascasarjana Universitas Negeri Jakarta, 2017)
This study aims to develop basic movement model based on interactive multimedia for elementary school students. This research and development presented in the form of interactive multimedia. The research method used is research and development using 10 steps from Borg and Gall While the subject of this research is the first grade students of elementary school. This study begins with the needs analysis, planning, product development, try out, revision, and final product. The result of this research showed that this product is appropriate for students in grade 1. It was confirmed by the test results of small group and large group that elucidate that the entire of models can be carried well. Consequently, it is showed that this model is essentially and effectively used by the first grader of elementary school students in increasing their ability especially in basic motor skills.Gain score obtained average score 0,59 which means that the comparison between pre-test score and post-test score differences is medium. Keywords: Development, Basic Movement, Interactive Multimedia, Elementary School